Ontological framework for standardizing and digitizing clinical pathways in healthcare information systems. (November 2020) - Alahmar, Ayman; Crupi, Matteo Ermando; Benlamri, Rachid
Highlights: An ontological framework for standardizing and digitizing clinical pathways (CPs) in healthcare information systems is proposed. The framework is based on a CP coding system compliant to SNOMED CT standard to facilitate data analytics. The proposed framework is implemented in a prototype Clinical Pathway Management System (CPMS) that was developed in collaboration with Thunder Bay Regional Health Sciences Centre (TBRHSC). The system was validated on a repository of patient records with ischemic stroke. This was performed with the help of domain experts from the Regional Stroke Unit. The results show that CPs can be fully standardized and digitized using SNOMED CT terms and codes, and the CPMS can work as an independent system, performing novel CP-related functions. CPs can be compared easily for auditing and quality management. The proposed framework is promising and contributes toward solving major challenges related to CP standardization, digitization, and inclusion in today's modern computerized hospitals. Abstract: Background and Objective: Most healthcare institutions are reorganizing their healthcare delivery systems based on Clinical Pathways (CPs). CPs are novel medical management plans to standardize medical activities, reduce cost, optimize resource usage, and improve the quality of service. However, most CPs are still paper-based and not fully integrated with Health Information Systems (HIS). More CP computerization research is therefore needed to fully benefit from CP's practical potentials. A major contribution of this research is the vision that CP systems deserve to be placed at the centre of HIS, because within CPs lies the very heart of medical planning, treatment and impressions, including healthcare quality and cost factors. Methods: An important contribution to the realization of this vision is to fully standardize and digitize CPs so that they become machine-readable and smoothly linkable across various HIS. To achieve this goal, this research proposes a framework for (i) CP knowledge representation and sharing using ontologies, (ii) CP standardization based on SNOMED CT and HL7, and (iii) CP digitization based on a novel coding system to encode CP data. To show the feasibility of the proposed framework we developed a prototype clinical pathway management system (CPMS) based on CPs currently in use at hospitals. Results: The results show that CPs can be fully standardized and digitized using SNOMED CT terms and codes, and the CPMS can work as an independent system, performing novel CP-related functions, including useful data analytics. CPs can be compared easily for auditing and quality management. Furthermore, the CPMS was smoothly linked to a hospital EMR and CP data were captured in EMR without any loss. Conclusion: The proposed framework is promising and contributes toward solving major challenges related to CP standardization, digitization, and inclusion in today's modern computerized hospitals.